Consumer Behavior / Seventh Edition - Blackwell Roger D.; Engel James F; Miniard Paul W (The Dryden Press, 1993)
The most influential textbook in making the study of behavioral science relevant to the business student. Introduction and Overview, Environmental Influences, Individual Differences, Psychological Processes, Consumer and Decision Processes and Behavior, Consumer Analysis and Marketing Strategy, Epilogue, Glossary, Index.